2011
DOI: 10.1172/jci57660
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin mediates stress-induced food-reward behavior in mice

Abstract: The popular media and personal anecdotes are rich with examples of stress-induced eating of calorically dense "comfort foods." Such behavioral reactions likely contribute to the increased prevalence of obesity in humans experiencing chronic stress or atypical depression. However, the molecular substrates and neurocircuits controlling the complex behaviors responsible for stress-based eating remain mostly unknown, and few animal models have been described for probing the mechanisms orchestrating this response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
352
6
20

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(408 citation statements)
references
References 69 publications
30
352
6
20
Order By: Relevance
“…This result is reminiscent of a recent study showing that ghrelin action on dopaminergic neurons is sufficient to drive food-reward in a context of chronic stress, referred to as 'comfort feeding' (Chuang et al, 2011). Our observations are also in line with a study showing that loss of AgRP neuron function promotes greater excitability of VTA dopamine neurons (Dietrich et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is reminiscent of a recent study showing that ghrelin action on dopaminergic neurons is sufficient to drive food-reward in a context of chronic stress, referred to as 'comfort feeding' (Chuang et al, 2011). Our observations are also in line with a study showing that loss of AgRP neuron function promotes greater excitability of VTA dopamine neurons (Dietrich et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…When access to palatable liquid diet was provided, the body weight of the AgRP-ablated mice was rapidly regained ( Figure 6C); furthermore, while control animals maintained caloric intake, the AgRP-ablated mice consumed more calories ( Figure 6D). Our finding that AgRP-ablated mice exhibit exaggerated hyperphagia on a palatable diet and greater anorexia during stress is consistent with the hypothesis that, in the absence of AgRP neurons, feeding is less motivated by energy demand and more sensitive to changes in stress and reward value (Chuang et al, 2011).…”
Section: Feeding Behavior In the Absence Of Agrp Neurons: A Model Ofsupporting
confidence: 88%
“…The VTA dopamine neurons express GHSR and respond to ghrelin by increasing the action potential frequency and the Acb dopamine release (Abizaid et al, 2006;Jerlhag et al, 2007). Also, rewarding foods-induced Acb dopamine release is reduced in GHSR knockout mice (Egecioglu et al, 2010), and selective GHSR expression in catecholaminergic cells, including the VTA dopamine neurons, is sufficient to mediate ghrelin-induced conditioned place preference for HFD (Chuang et al, 2011). The possibility that ghrelin signaling could involve a form of central sensitization that affects the intake of palatable foods may be clinically relevant and deserves future studies as alterations in ghrelin signaling seem to contribute to the magnitude of binge eating episodes in some, but not all, patients with binge eating disorder (Geliebter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that this interaction extends beyond the homeostatic hypothalamic regulation of food intake and may involve hedonic feeding behaviour. Indeed, recent studies have identified the ghrelinergic system as a key player in hedonic food intake behaviours, including the motivational drive to eat, the rewarding aspects of food intake and the stress-induced ingestion of palatable foods [84][85][86][87][88][89][90][91][92] . Interestingly, the 5-HT2C receptor has also been implicated in reward-related behaviours 93,94 , which may explain some overlapping functionalities with the GHS-R1a receptor including involvement in the hedonic regulation of food intake.…”
Section: Specific 5-ht2c Receptor Agonism Attenuates Ghrelin's Orexigmentioning
confidence: 99%